Pengaruh Faktor Sarana dan Prasarana Terhadap Pendapatan Masyarakat Nelayan (Studi di Desa Olele Kecamatan Kabila Bone Kabupaten Bone Bolango) - Irawati Abdul (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The objective of this research is to analyze how much the influence of infrastructure availability to the income of fisheries at Olele Village, Kabila Bone Sub-District, Bone Bolango Regency. The Method used in this research is random sampling to determine the location is intended and than used purposive to determine the sample of population at that village.  The result of this research are Road infrastructure is significant about 0,05 (0,02) means that it’s influence in to the in-come of Fisheries, transportation factor have influenced about 0,05 (0,08) in to the Fisheries in-come, economy activities like market is influence also to the fisheries in-come, Health and education factors have influenced about 0,5 (0,01) and 0,05 (0,01) in to the fisheries in-come, for education and electric power factors also influenced in to the fisheries in-come, water pump, sport square and praying building have also influenced significantly in to the in-come of fisheries. Keywords: Infra and Supra structure and In-come of Fisheries